Towards accurate prediction of catalytic activity in IrO2 nanoclusters via first principles-based variable charge force field1. Issue 37 (7th October 2015) - Sen, F. G.; Kinaci, A.; Narayanan, B.; Gray, S. K.; Davis, M. J.; Sankaranarayanan, S. K. R. S.; Chan, M. K. Y.
<x xml:space="preserve">Abstract</x> DFT-based variable-charge force field (MS-Q) developed to accurately predicted bulk and nanoscale properties of IrO2. Catalytic properties pertaining to oxygen reduction reaction found to depend on the coordination and charge transfer at the IrO2 nanocluster surface.